Performance Evaluation of Membrane Bioreactor Operational Design in Sewage Treatment Plant using GPS-X Software - Dawood, Ali S.; Omar, Fatehah M.; Baker, Amera G.; Karim, Hawbash H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study evaluates the operational performance of a full-scale membrane bioreactor wastewater treatment plant located in Kuala Lumpur using GPS-X 8.0 simulation software. Key performance indicators–including mixed liquor suspended solids (MLSS), transmembrane pressure (TMP), dissolved oxygen, and effluent total suspended solids (TSS)were monitored over 30 days. The simulations were conducted using the advanced mode and calibrated with actual plant data. Results show that although the plant complies with Malaysian effluent discharge standards, it operates well below its design capacity, with MLSS levels significantly lower than recommended. This operational underload contributes to increased energy consumption and reduced treatment efficiency, particularly in terms of TSS and chemical oxygen demand removal.